Tim-3 as a diagnostic and prognostic biomarker of osteosarcoma - Wenhui Ge; Jing Li; Wenhao Fan; Delong Xu; Shangfei Sun (Tumor Biology)
Osteosarcoma is the most frequent primary bone tumor that affects adolescents and children. However, diagnostic and prognostic biomarkers for osteosarcoma remain lacking. (Tim-3) T-cell immunoglobulin domain and mucin domain-3, which negatively regulates T cell helper (Th1) cells and affects cytokine expression, has attracted increasing attention due to its critical role in regulating both adaptive and innate immune cells. In this study, we evaluated serum soluble Tim-3 level in osteosarcoma patients to explore its diagnostic and prognostic value for this particular malignancy. Serum soluble Tim-3 level was measured with enzyme-linked immunosorbent assay in 120 osteosarcoma patients, 120 benign bone tumors patients and 120 healthy controls, followed by analysis of the correlation with clinic pathological characteristics. Receiver operating curves, Kaplan-Meier curves, and log-rank analyses as well as Cox proportional hazard models were used to evaluate the diagnostic and prognostic significance. Serum solubleTim-3 level was remarkably elevated in osteosarcoma patients. Osteosarcoma patients with larger tumor size, late stages and distant metastases were accompanied with higher levels of Tim-3. ROC/AUC analysis indicated thatTim-3 served as a reliable marker to distinguish healthy participants from Tim-3 patients. Osteosarcoma patients with higher Tim-3 had relatively lower survival. Multivariate analyses for overall survival revealed that high serum soluble Tim-3 level was an independent prognostic factor for osteosarcoma. Furthermore, Tim-3 levels of CD8+ and CD4+ T cells were elevated in peripheral circulation of osteosarcoma patients. Therefore, It was indicated in our research that elevated serum soluble Tim-3 level might be a novel potential diagnostic and prognostic biomarker for osteosarcoma patients.